Traumatic compressive stress inhibits osteoblast differentiation through long chain non‐coding RNA Dancr. Issue 11 (18th April 2020) - Lu, Qian; Xu, Weizhe; Liu, Linyi; Zhou, Xuedong; Ye, Ling; Song, Dongzhe; Zhang, Lan; Huang, Dingming
Abstract: Background: Occlusal trauma is an important local contributing factor aggravating periodontal pocket and alveolar bone absorption in periodontal diseases. Our previous studies have found that occlusal trauma inhibited osteogenic differentiation through nuclear factor (NF)‐κB signaling. To further investigate the underlying mechanism, the aim of this study was to explore the role of long chain non‐coding differentiation antagonizing non‐protein coding RNA (Dancr) in the inhibitory effect of traumatic stress on osteoblast differentiation. Methods: We took the MC3T3‐E1 cells as object in vitro research and stimulated cells with simple stress load, Dancr‐siRNA + stress load, Dancr overexpression‐plasmid + stress load. Quantitative real‐time polymerase chain reaction was used to detect the RNA expression levels of Dancr, alkaline phosphatase (Alp) and Runt‐related transcription factor 2 (Runx2). The protein expressions of Alp and Runx2 were tested by Western blot and the activity of Alp was qualitatively demonstrated by Alp staining. In addition, Western blot was performed to investigate the role of Dancr in affecting NF‐κB signaling pathway. Results: Traumatic compressive stress inhibited the expressions of Alp, Runx2, andDancr in MC3T3‐E1 cells. Stress‐induced inhibition of osteoblast differentiation was promoted after silencing Dancr. Overexpression of Dancr could alleviate the inhibitory effect of traumatic force on osteoblast differentiation to some extent. Furthermore, NF‐κB signaling was activated after silencing Dancr, and the activated effect of traumatic force on NF‐κB signaling could be alleviated through overexpression of Dancr to some extent. Conclusion: Traumatic compressive stress can indirectly activate the NF‐κB signaling through downregulation of Dancr, thereby inhibiting osteogenic differentiation.